A defect-driven atomically dispersed Fe–N–C electrocatalyst for bifunctional oxygen electrocatalytic activity in Zn–air batteries. Issue 9 (3rd February 2021) - Zhang, Jie; Chen, Jinwei; Luo, Yan; Chen, Yihan; Luo, Yingjian; Zhang, Chenyang; Xue, Yali; Liu, Honggang; Wang, Gang; Wang, Ruilin
Abstract : The optimized Fe–N–NDC-1-900 exhibits robust anchoring ability to immobilize atomic Fe species with abundant Fe–N4 sites, demonstrating excellent electrocatalytic activity in both the ORR and OER. Abstract : This work proposes a strategy to synthesize N-doped defective carbon (NDC), followed by trapping the FePc precursor. After pyrolysis, the optimized Fe–N–NDC-1-900 exhibits robust anchoring ability to immobilize atomic Fe species with abundant Fe–N4 sites, demonstrating excellent electrocatalytic activity in both the oxygen reduction reaction (ORR, E 1/2 = 0.89 V, E onset = 1.06 V) and oxygen evolution reaction (OER, E 10 = 1.58 V). It also shows outstanding stability and delivers faster kinetics in oxygen electrocatalysis. Furthermore, the bifunctional Fe–N–NDC-1-900 is fabricated for a Zn–air battery, which demonstrates a high open-circuit voltage of 1.479 V, power density of 266 mW cm −2, specific capacity of 786 mA h gZn −1, and excellent reversibility with long-term cycling. DFT suggests that the high ORR activity is mainly ascribed to its high electronegativity and small energy barriers, produced by the adjacent pore defects and optimal charge redistribution.